If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -15 + 8 + -10y + 1 = 8 Reorder the terms: -15 + 8 + 1 + -10y = 8 Combine like terms: -15 + 8 = -7 -7 + 1 + -10y = 8 Combine like terms: -7 + 1 = -6 -6 + -10y = 8 Solving -6 + -10y = 8 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -10y = 8 + 6 Combine like terms: -6 + 6 = 0 0 + -10y = 8 + 6 -10y = 8 + 6 Combine like terms: 8 + 6 = 14 -10y = 14 Divide each side by '-10'. y = -1.4 Simplifying y = -1.4
| 120=37.94+0.50x | | -9x+9=27 | | 6(4x+3)=92 | | 62=3(5)b+2 | | K+3.9=0.7 | | 2x+1=-1+4 | | x+x+20+2X(x+20)=160 | | X^3+100=0 | | 0.6(x+0.2)=1.8 | | 2x+1=4-1 | | X(x+3)=1120 | | 4x+3+6x=92 | | 2x+1=4+1 | | 4x+(6x-3)=92 | | (4x+3)+(6x-3)=92 | | 4x+6x+3=92 | | 1.76g-9=.68 | | (-11)-(-12)= | | 2x+1=-4+1 | | -5x-7=19 | | 2x-7+4x=2(2x+7)+24 | | 24x-6=-27+21x | | 10x*5=15x-30 | | -140=4(5-4r) | | -2v+5+6v=1+5v+3 | | y=-0.01x^2+0.7x+6 | | 3x-9+1=-1 | | 4x-16=-18 | | 9-(4s-3)+6s= | | 5x-5+4x+20=180 | | 3(x+4)=3(x+7) | | 3(2)=2x+13 |